The Meaning of (Rizq) between the Quranic Situation and Usage - Rashid, Saad Ali (Journal of Tikrit University for Humanities, 2025)
This research aims to find out the meaning of rizq (provision) in light of the duality of status and usage in the Holy Qur’an, because this duality has a great importance in revealing the precise meanings of words. Rizq is one of the words that are repeatedly mentioned in the Mighty Book of Allah, and it requires research to reveal its implications and its precise meanings, to deeply understand the Qur’anic texts. The research made it clear that the meanings of the word (provision) varied according to the multiple contexts and rhetorical positions in which it was mentioned. The context had a clear impact in diversifying the meaning of sustenance, but all of its connotations were related and connected to its original positive meaning, and it clarified the prominent role of the transmitted metaphor in conveying its meaning (livelihood) from its positive meaning to its contextual usage meanings.